Organizational and activational effects of estrogenic endocrine disrupting chemicals - Ellen K. Silbergeld; Jodi A. Flaws; Ken M. Brown
Endocrine disruption is a hypothesis of common mode of action that may define a set of structurally varied chemicals, both natural and synthetic. Their common mode of action may suggest that they produce or contribute to similar toxic effects, although this has been difficult to demonstrate. Insights from developmental biology suggest that development of hormone sensitive systems, such as the brain and the genitourinary tract, may be particularly sensitive to EDCs. Because these systems are both organized and later activated by hormones, the brain and vagina may be valuable model systems to study the toxicity of EDCs in females and to elucidate mechanisms whereby early exposures appear to affect long term function.